INFLUENCE OF GAME ACTIVITIES ON THE FORMATION OF INTERPERSONAL RELATIONSHIPS OF PRESCHOOL CHILDREN - Skomorovska, Iryna; Ivaniychuk, Bohdana (Mountain School of Ukrainian Carpaty, 2023)
The article reveals the problem of the formation of interpersonal interaction of preschoolers during game activities. Several definitions of the term «interpersonal interaction» are presented, in particular, it is indicated that these are subjective connections and relationships between people that arise under the conditions of living together or performing joint activities. It is noted that communication between preschoolers and adults differs from communication between peers of preschool age. Communication between an adult and a child has signs of cognitive, educational, educational influence. In such relationships, an adult usually takes a dominant position. A preschooler’s communication with peers is more free, emotional, creative, not limited by the instructions of an adult. It is in such interaction that the child learns to build relationships with others. It has been proven that the inclusion of children in communication with peers is a necessary condition for a child’s development. A preschooler masters moral norms; learns to understand the opinion of others, if it is different from his own; develops creatively, looks for non-standard ways of establishing interaction; learns to organize joint activities. It is indicated that joint game activity contributes to the establishment of interpersonal interaction between peers and contributes to their socialization. In the game, a preschooler can realize various social roles, reflecting the previously acquired experience of social behavior. During game activities, favorable conditions are created for the development of joint interaction and communication skills, in particular, when it comes to choosing the theme of the game, the plot, the distribution of roles, the choice of toys or substitute objects, etc. Preschoolers unconsciously implement various models of behavior that they have observed before and thus are able to reflect the actions and actions of adults in joint game activities. The relations that arise between preschoolers in a story role-playing game are characterized. In particular, real relationships that demonstrate real relationships between children and are aimed at solving organizational issues that arise before or during play activities. Role-playing is aimed at the realization by the preschooler of the role of one or another character in the game.